Too sweet to eat: Exploring the effects of cuteness on meat consumption. (1st January 2018) - Zickfeld, Janis H.; Kunst, Jonas R.; Hohle, Sigrid M.
Abstract: Although daily meat consumption is a widespread habit, many individuals at the same time put a high value on the welfare of animals. While different psychological mechanisms have been identified to resolve this cognitive tension, such as dissociating the animal from the consumed meat or denying the animal's moral status, few studies have investigated the effects of the animal's appearance on the willingness to consume its meat. The present article explored how the perception of cuteness influences hypothetical meat consumption. We hypothesized that cuter animals would reduce the willingness to consume meat, and that this relationship would be mediated by empathy felt towards the animal. Across four pre-registered studies sampling 1074 US and Norwegian participants, we obtained some support for this prediction in the US but to a lesser degree in Norway. However, in all studies an indirect mediation effect of cuteness on meat consumption going through empathy towards the animal was observed. We also explored possible moderating and additional mediating mechanisms of trait pro-social orientation, caretaking intentions and sex effects for which we found mixed evidence. Theoretical and practical implications of the findings are discussed.